PENGARUH COUNTRY OF ORIGIN, BEAUTY INFLUENCER, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KECANTIKAN ASAL KOREA SELATAN (Studi kasus pada Brand InnisFree di Jakarta) - Mutiara Angelika, (2022)
The formulation of the problem is to know how the influence of country of origin, beauty influencer and product quality against the purchase decision of InnisFree's products. From the results of the research can be known responses of respondents about country of origin, beauty influencer and product quality can be said quite well which resulted in good decisions purchase of InnisFree's product. The type of research conducted is quantitative research. This research is quantitative with primary data sources. The targeted populations are people who had used or are using the InnisFree's product and follow several influencers on social media. The sample used is 100 respondents. The sampling technique used non-probability sampling with purposive sampling method. The data collection that's used for this research was spreading out an online questionnaire using Google Form and broadcast it through line, WhatsApp and Instagram. This study uses the SEM method with the software used is SmartPls 3.0. This research resulted to, country of origin has a positive and significant effect on purchasing decisions with an original sample value of 0.320 and probability value of 0.000. Beauty influencer has a positive but doesn't significantly effect the purchasing decisions with an original value of 0.189 and probability value of 0.056. Lastly, product quality has a positive value and significant effect on purchasing decisions with an original sample value of 0.472 and probability value of 0.000.